Influência do veículo na remoção da pasta tri antibiótica do canal radicular - Yamanari, Guilherme Hiroshi [UNESP] (2015)
AIM: This study evaluated the interference of the triple antibiotic paste vehicle on its removal from the root canal using needle irrigation with or without passive ultrasonic irrigation (PUI). METHODS: Sixty root canals were prepared up to F4 ProTaper and were filled with triple antibiotic pastes (TAP) prepared with macrogol plus propylene glycol, distilled water, or propylene glycol. After 4 weeks of stove storage, needle irrigation with 2.5% sodium hypochlorite with or without PUI was used for TAP removal. The roots were longitudinally split and the amount of remaining antibiotic pastes and cleaning of the dentinal tubule were evaluated under a stereomicroscope and SEM. The data were statistically evaluated using the Kruskal Wallis and Dunn's tests (p = .05). RESULTS: In the middle and apical thirds, TAP with propylene glycol remained more than that prepared with distilled water (p < .05). Distilled water or macrogol plus propylene glycol were similar independently of the root canal third. The use of PUI did not improve the removal of the TAP (p > .05). There were no statistically significant differences between the coronal, medium or apical thirds (p > .05). CONCLUSIONS: None vehicle allowed the complete paste removal and cleaning of the dentinal tubule from the root canal and despite the use of PUI. Distilled water or macrogol plus propylene glycol as vehicle favored smaller remnant of TAP in the apical and middle thirds